Афганистан: оппозиция и власть (60-70-е гг. XX в.) - Слинкин, М.Ф. (Культура народов Причерноморья, 2005)
In this book the author of the basis of a great deal of the original Afghan, foreign and home documents and materials investigates ideological and political views and stands of the Afghan antigovernment opposition forces in the 1960-1970s, deeply analyzes the emergence and influence of the left factor over social and political struggle in the country and also shows trends of the social-economic, political, ideological and cultural development in Afghanistan in the mentioned years. The great attention in the work is given to the description of the ethnic-national, religious, language and other peculiarities of the country and psychology, manners, customs and mode of life of the Afghans. By this book the author puts into scientific circulation many unknown or little known documents and materials from private and party-state archives? Afghanistan's official and underground publications and also eyewitnesses of those who actively participated in the described opposition movements. At the end of the book there are given selectic biographic sketches of some well-known Afghan statesmen, political, religious and military figures of the above named period.